„Wrzesień żagwiący” (Scorching September) by Melchior Wańkowicz. Against the Backdrop of Post-war Memoirs and the Historiography of the Semptember Campaign - Bobryk, Roman (Porównania, 2025)
Wrzesień żagwiący (Scorching September) is a book published in 1947 regarded as one of the most significant achievements in Polish wartime reportage. The book was written in parts, with the first section published in the early 1940s, others released during the war, and the remaining sections after its end. The different timeframes in which the parts were written suggest that the author had a heterogeneous approach to his descriptions. The approach applies to the narrator’s perspective and the participant’s accounts of the 1939 fight. The book’s publication in the West allowed Wańkowicz to highlight the role of the Soviet Union in the 1939 Defensive War. The comparison between his accounts and the works of military historians and memories of the participants of the Polish September Campaign reveals some structural similarities in the content arrangement. One might also argue that some later authors drew upon Wańkowicz’s work as a source for their own narratives.